Measuring the quality of nursing clinical placements and the development of the Placement Evaluation Tool (PET) in a mixed methods co-design project - Simon Cooper; Robyn Cant; Donna Waters; Elise Luders; Amanda Henderson; Georgina Willetts; Marion Tower; Kerry Reid-Searl; Colleen Ryan; Kerry Hood (BMC, 2020)
Abstract Background The quality of nursing clinical placements has been found to vary. Placement evaluation tools for nursing students are available but lack contemporary reviews of clinical settings. Therefore, the aim of this study was to develop a feasible, valid and reliable clinical placement evaluation tool applicable to nursing student placements in Australia. Methods An exploratory mixed methods co-design project. Phase 1 included a literature review; expert rating of potential question items and Nominal Group Technique meetings with a range of stakeholders for item development. Phase 2 included on-line pilot testing of the Placement Evaluation Tool (PET) with 1263 nursing students, across all year levels at six Australian Universities and one further education college in 2019-20, to confirm validity, reliability and feasibility. Results The PET included 19-items (rated on a 5-point agreement scale) and one global satisfaction rating (a 10-point scale). Placements were generally positively rated. The total scale score (19 items) revealed a median student rating of 81 points from a maximum of 95 and a median global satisfaction rating of 9/10. Criterion validity was confirmed by item correlation: Intra-class Correlation Co-efficient ICC = .709; scale total to global score r = .722; and items to total score ranging from .609 to .832. Strong concurrent validity was demonstrated with the Clinical Learning Environment and Supervision Scale (r = .834). Internal reliability was identified and confirmed in two subscale factors: Clinical Environment (Cronbach's alpha = .94) and Learning Support (alpha = .96). Based on the short time taken to complete the survey (median 3.5 min) and students' comments, the tool was deemed applicable and feasible. Conclusions The PET was found to be valid, reliable and feasible. Use of the tool as a quality assurance measure is likely to improve education and practice in clinical environments. Further international evaluation of the instrument is required to fully determine its psychometric properties.